Guava fibre characterization and effects on digestibility, fermentation products, gastrointestinal transit time and palatability of dry diets for dogs - Monti, Mariana [UNESP]; Loureiro, Bruna A. [UNESP]; Pedreira, Raquel Silveira [UNESP]; Mendonça, Fernanda S. [UNESP]; Putarov, Thaila C. [UNESP]; Villaverde, Cecilia; Carciofi, Aulus Cavalieri [UNESP] (Wiley, 2024)
The use of fruit fibres as a way of reusing industrial waste is attractive and necessary, increasing the efficiency and reducing the environmental impact of the industry. This study characterized guava fibre as a fibrous ingredient and evaluated its effects when included in extruded diets for dogs on nutrient digestibility, faecal traits, fermentation products, gastrointestinal transit time and palatability. Four diets were formulated: CO (control diet, no fibrous ingredients added), GF3 (3% guava fibre), GF6 (6% guava fibre) and GF12 (12% guava fibre). The guava fibre was added to diets in replacement of maize, with small adjustments in the other ingredients to ensure similar contents of protein and fat. The diets were fed to 24 adult Beagle dogs (6 per diet) during 15 days for adaptation followed by 15 days for assessment of digestibility, fermentation end products and gastrointestinal transit time. The palatability of G6 and G12 treatments was evaluated against the CO by the two-pan test. Results were compared by analysis of variance and polynomial contrasts according to the guava fibre inclusion level (p < 0.05). The addition of guava fibre did not change nutrient intake except for the increase on dietary fibre (p < 0.001). Fibre inclusion resulted in a quadratic reduction in total tract apparent digestibility for dry matter, organic matter, crude protein and crude energy (p < 0.001), and on the metabolizable energy content of the foods (p < 0.001). Guava fibre addition did not change the faecal concentration of ammonia, lactic acid, faecal pH and branched chain fatty acids but it decreased acetic and propionic acids concentration (p < 0.01). The inclusion of 12% guava fibre did result in a faster transit time (p = 0.046) compared to the control diet. Guava fibre can be characterized as a novel insoluble non-fermentable fibre source that could be safely used in levels up to 12% in canine extruded diets.
Keywords: acetate; fruit fibre; propionate; Psidium guajava